Investigation of the formation features of the 2P/RS phase in alumonickelates Sr3Ni2 – x AlxO7 – δ (0.5 ≤ x ≤ 0.75) - Kharlamova, Inga M.; Makhnach, Leonid V.; Usenka, Alexandra E.; Korobko, Evguenia V.; Pankov, Vladimir V. (Journal of the Belarusian State University. Chemistry, 2023)
In the present work the formation features of the crystal structure of the 2P/RS phase (P is a layer of perovskite, RS is a layer of rock salt) were investigated and the optimal conditions for the synthesis of the phase in Sr3Ni2 – xAlx O7 – δ (0.5 ≤ x ≤ 0.75) solid solutions were established. The role of intermediate oxide compounds formed at the stage preceding the formation of these solid solutions was demonstrated.  The following binary oxides and solid solutions derived from them were found as intermediate compounds in the temperature range 900–1100 °C: Sr9Ni7O21, Sr3Al2O6, Sr9Ni7 – x Alx O21 (0 < x ≤ 0.2), Sr3Al2 – x Nix O6 (0 < x ≤ 0.1). Oxide compounds Sr9Ni7 – x Alx O21 (0 < х ≤ 0.2) decomposed at 1030 °C in air and at 1120 °C in an oxygen flow.  The use of intermediate compounds as precursors made it possible to optimise the process of formation of the 2P/RS phase, i. e. to decrease the synthesis temperature by 30–40 °C and to reduce the synthesis duration by 8–10 h.
Keywords: strontium alumonickelates; precursors; solid solutions; Ruddlesden – Popper phases